Year five pupils’ mental model of environment / Kavitha Maslamany - Kavitha , Maslamany (2020)
In the current society, pupils are given less opportunity to discover the natural world around them. This has resulted in ‘nature deficit disorder’ among the pupils especially among those who are living in urban areas which are surrounded by the built environments. This becomes worse when pupils get less exposure to environmental education in schools where they learn environmental concepts as disconnected pieces of information. Pupils who are unable to comprehend the environment as a complex and interconnected system will have less awareness of environmental problems. Studying pupils’ mental models of the environment enable teachers to understand pupils’ conceptualization of how the environment works as a system. Therefore, this study has been carried out to investigate the Year Five pupils’ mental models of the environment and their relationships with their perceived pro-environmental behaviours. The present study has also investigated the factors that have influenced pupils’ mental models of environment. A descriptive survey research design was employed in this study. The sample comprised 104 Year Five pupils from one of the schools in an urban area at Petaling Jaya. Pupils’ mental models or images of the environment were elicited using Draw-an-Environment Test (DAET) and were analysed using a 4-factor analytic rubric (DAET-R). Mental Model Factors and Environmental Behaviour Questionnaire (MMFEB) which consisted of two-parts were used to identify the factors that had influenced the Year Five pupils’ mental models and their perceived pro-environmental behaviours. Descriptive statistics, Pearson correlation, content analysis and regression were used to analyse the data obtained through MMFEB. The findings revealed that 65% of the pupils in this study did not include human elements in their drawings. Overall, pupils held a moderate level of environmental mental models which is an incomplete mental model. Four types of mental models namely, Model 1 (a Perfect Environment), Model 2 (Interaction Between Human and Environment), Model 3 (Environmental Problems) and Model 4 (Solving Environmental Problems) were present among the pupils. The finding from the correlations further revealed that pupils with a higher level of mental model tended to demonstrate more positive pro-environmental behaviour. The finding further reveals that that school, experience, environmental problems and socio-culture factors have influenced the level and the types of pupils’ mental models of environment. The present study also confirms that drawings can serve as an appropriate tool to gain insights into pupils’ mental model of the environment and the relationshipwith human. Such insights are important for an impactful teaching and learning of environmental education. Teachers may also use pupils’ drawings to develop more complete mental models. A holistic view of developing curriculum and instruction is recommended to provide learning opportunities for pupils to understand the definition of environment.